A qualitative and quantitative approach in evaluating writing self-efficacy - Jalaluddin, Ilyana (International Educative Research Foundation and Publisher, 2014)
This study aimed to evaluate the rural area learners’ writing self-efficacy using two different approaches which are qualitative and quantitative approach. Basically, it is a case study where three form four students and a teacher were involved in the research for six months. In this study, the learners’ writing self-efficacy was investigated using a combination of quantitative (writing self-efficacy scale adapted from Bottomley, Henk, & Melnick, 1997) and qualitative (classroom observation). Classroom observation was based on three characteristics: persistence in accomplishing language tasks, self-awareness of English proficiency, and willingness to engage in language activities. These characteristics which were used by Wang and Pape (2007) were based on Bandura’s (1997) concept of self-efficacy. Overall, this study did not focus on the score of WSE scales alone but also placed a heavy emphasis on the perceptions and actions of the form four students and teacher. This was done through 15 non-participant classroom observations, 10 interviews with each of the three students and 10 teacher’s interviews to understand the participants’ self-efficacy phenomena in their learning to write. Findings showed that the combination of different method of collecting data for writing self-efficacy was a feasible way in explaining rural learners’ writing self-efficacy development.